European politics a comparative introduction - Bale, Tim 1965- (Palgrave Macmillan, 2005)
A thematically-organised introduction to the governance and politics of Europe, this text provides an accessible guide to both the institutions and the issues that matter in a continent where the boundaries between East and West, and between domestic andEU affairs are breaking down.
Keywords: Europäische Union; European Union; Politieke situatie; Politieke stelsels; Vergelijkende politicologie; Politik; Politische Situation; Comparative government; Europa; Europe -- Politics and government